The Influence of pH on the Lipase Digestion of Nanosized Triolein, Diolein and Monoolein Films - Humphreys, Ben A.; Campos-Terán, José; Arnold, Thomas; Baunsgaard, Lone; Vind, Jesper; Dicko, Cedric; Nylander, Tommy (Frontiers in Soft Matter, 2022)
Herein we studied the processes at the liquid aqueous interface at pH 7 and 8.5 during Thermomyces lanuginosus lipase-catalyzed hydrolysis of nanosized tri-, di- and mono-olein films deposited on a planar substrate. By employing a combination of ellipsometry, QCM-D and ATR-FTIR, we were able to reveal the physical properties of the thin films at high time resolution throughout the initial hydration and subsequent digestion, as well as the main chemical species present before and after lipolysis. The ATR-FTIR results showed that the degree of digestion and protonated state of the oleic acid produced in the reaction are highly dependent on the pH of the aqueous solvent. Furthermore, the ellipsometry and QCM-D results reveal that the duration of the lag phase observed before lipolysis was detected and the magnitude and type of changes to the physical properties of the thin films throughout digestion was influenced by whether the initial substrate consisted of tri-, di- or mono-olein.